flaAII (motC, cheV) of Salmonella typhimurium is a structural gene involved in energization and switching of the flagellar motor. - Dean, G E (1983)
The flaAII gene of Salmonella typhimurium has also been termed motC and cheV, because defective alleles may give rise to a nonflagellate, paralyzed, or nonchemotactic phenotype. We isolated a temperature-sensitive motility mutant (MY1) and have found that the mutation occurs in the flaAII gene. In temperature-jump experiments, MY1 could be converted from highly motile to paralyzed within 0.5 s, demonstrating that flaAII is a structural gene whose product is immediately essential for motor rotation. The mutant, although chemotactic at permissive temperatures (less than 36 degrees C), had a higher clockwise rotational bias than did the wild type; it can therefore be regarded simultaneously as motC(Ts) and cheV (tumbly). The only previously reported S. typhimurium cheV mutant was smooth-swimming. A shift toward counterclockwise bias accompanied loss of rotational speed in the restrictive temperature range. This result, by analogy with known proton motive force effects on motor switching, further indicates a central role of the flaAII (motC, cheV) protein in the energy transduction and switching process. Since there is no evidence associating it with the isolable entity known as the basal body, it may reside at the cytoplasmic face of the flagellar motor.